2020
DOI: 10.5194/egusphere-egu2020-11904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards a Pan-European snow cover and melt extent product from Sentinel-1 SAR and Sentinel-3 SLSTR Data

Abstract: <p>The synergistic use of data from different satellites of the Sentinel series offers excellent capabilities for generating high quality products on key parameters of the global climate system and environment. A main parameter for climate monitoring, hydrology and water management is the seasonal snow cover. In the frame of the ESA project SEOM S1-4-SCI Snow, led by ENVEO, we developed, implemented and tested a novel approach for mapping the total extent and melting areas of the seasonal snow co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Across all tests, the liquid water content was among the strongest correlation values (see appendixes A3, A4 and A5). This coincides with the ongoing understanding of the measured signal loss being related to the amount of liquid water within a snowpack (e.g., Lund et al, 2022;Nagler et al, 2021). With increasing water presence, radar attenuation increases and measured signal decreases.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Across all tests, the liquid water content was among the strongest correlation values (see appendixes A3, A4 and A5). This coincides with the ongoing understanding of the measured signal loss being related to the amount of liquid water within a snowpack (e.g., Lund et al, 2022;Nagler et al, 2021). With increasing water presence, radar attenuation increases and measured signal decreases.…”
Section: Discussionsupporting
confidence: 86%
“…Adaptive thresholds based on the underlying land cover class (Liu et al, 2022) have recently been suggested. However, we have used the established and widely applied threshold of 2 dB for Sentinel-1 data (Nagler et al, 2021(Nagler et al, , 2016, results indicated in Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…As moisture increases, the SAR backscattering reduces in intensity since part of it is absorbed by the water particles [43,80,81]. The followed approach foresees the use of two images (i) a reference image acquired during snow-free or dry conditions [19,34,47,80,82]; and (ii) an image of the period of interest, such as the melting season. The difference of the two images allows the detection of main changes such as those related to wet snow presence and reduces the influence of other factors such as the topography.…”
Section: Sar Processingmentioning
confidence: 99%
“…Active sensors are commonly used in local scale application. In particular, the new Sentinel-1 (S-1) SAR constellation, which has a dual polarization capability, very short revisit times, high spatial resolution, rapid product delivery, has open access for all imagery [46], and has become the most common source used in different applications that exploit wet snow information [19,[47][48][49].…”
Section: Introductionmentioning
confidence: 99%